(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This research identifies several promising methods and technologies for CSA for Kyrgyz Republic. These practices can contribute to the diversification of farming systems and income sources, as well as help to overcome the difficulties caused by climate change in attracting investments for the development of the agricultural sector. Long-term investment in agricultural infrastructure, building the capacity of farmers and value chains, and implementing CSA policies and programs are important elements in promoting sustainable agricultural development in Kyrgyz Republic.